The impact of economic crisis on transformation of regional structures in France - Dorocki, Sławomir (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
It is recognized that the financial crisis, which was the symbolic beginning of the bankruptcy of Lehman Brothers in September 2008, first hit the most advanced countries. A common phenomenon in European countries has become a trend reversal in the labour market, manifesting a decrease in the number of employees. The decline in employment was almost two times higher in developed countries than in developing countries. In developing countries the crisis hit the hardest into export-oriented industries, while in developed countries, into manufacturing industries and trade. Dismissals in building industry relate to a similar extent to different regions of developed countries and developing countries. Economists note that the economic crisis and the differences in pace of its impact on the economy of individual units reduced in recent years the gap between rich regions and those lagging behind. The study was an attempt to present regional differences in the impact of financial crisis of economy in France on the basis of data characterizing the change in general employment and industry, services and trade. The particular attention was directed to the relationship between the extent of the impact of the crisis on employment size and the degree of economic development.